When I feel good about myself - Spelman, Cornelia (NEW YORK : Scholastic, 2003)
A young guinea pig explains that self-confidence comes from learning new things without being afraid of making mistakes and to remember that everyone has different qualities that make them lovable.
Keywords: Self-confidence; Individuality